Social dimension of European Union and the situation of the Labour Law in the member states: Evaluation of the spanish experience - Baylos, Antonio; Trillo, Francisco (Revista de Evaluación de Programas y Políticas Públicas, 2013)
The EU decision to take into account only economical origin and discard the social one, adopting the Pact of Euro as the best –and only- way to get over the crisis, has the mistake to confuse origin and consequences. As known, the main content of the Pact of Euro is addressed to reduce public deficit. As a result of these policies, almost all EU-27 countries have been converting private debt in public debat, cutting public spending in Education, Health and Social Service and bailing out several banks, worsening crisis social causes. This idea, obviously, is expressed in another way, affirming that in order to maintain Social State is firstly necessary to control public deficit. But in fact, after five years of austerity measures, there are many doubts about sincerity of these (neoliberalism) policies.ResumenLa decisión de la UE de tener en cuenta sólo el origen económico, descartando el social, adoptando el Pacto del Euro como la mejor y única manera de superar la crisis, tiene el error de confundir el origen y sus consecuencias. Es sabido que el contenido principal del Pacto del Euro se dirige a reducir el déficit público. Como resultado de estas políticas, casi todos los países de la UE-27 han estado convirtiendo la deuda privada en debate público, reduciendo el gasto público en Educación, Salud y Servicios Sociales y con el rescate de varios bancos, con un empeoramiento de las causas sociales debido a la crisis. Esta idea, por supuesto, se expresa de otra manera, afirmando que con el fin de mantener el Estado social es una parte necesaria para controlar el déficit público. Pero, de hecho, después de cinco años de medidas de austeridad, hay muchas dudas acerca de la sinceridad de estas políticas (neoliberalismo).